An analysis of the determinants of solid waste disposal in Brazil - Matos , Laynara Santos de; Almeida , Roselaine Bonfim de; Silva , Jonathan Gonçalves da; Carvalho , Leandro Vinícios (Technical and Scientific Journal Green Cities, 2025)
Objective – To analyze the evolution of urban solid waste (MSW) management in Brazil between 2014 and 2022 and to identify the socioeconomic factors that determine access to household waste collection.Methodology – This quantitative study combines descriptive analysis of data from the National Sanitation Information System (SNIS) with an econometric model (logit) based on the 2015 Brazilian National Household Sample Survey (PNAD).Originality/Relevance – The research integrates sectoral analysis with empirical identification of the factors influencing access to waste collection services, highlighting critical inequalities within the context of non-compliance with the Brazilian National Solid Waste Policy (PNRS).Results – The sector shows stagnation in selective waste collection (available in only 32.2% of municipalities in 2022) and a 21.2% increase in the number of open dumps. The logit model indicates that residing in an urban area increases the odds of having waste collected by 125 times. Education, income, and being White also positively and significantly impact the probability of access to the service.Theoretical/Methodological Contributions – The study provides an integrated sectoral and econometric analysis, confirming the influence of social determinants on access to essential environmental services.Social and Environmental Contributions – It underscores the need for targeted public policies to reduce inequalities and promote environmental justice, aligning MSW management with the principles of the PNRS.
Keywords: Solid Waste; Inequality; Nacional Solid Waste Policy